African literature, animism and politics - Rooney, Caroline (Routledge research in postcolonial literatures, 2000)
"African Literature, Animism and Politics considers the ways in which the inventions of Africa differ from inventions of the Orient. Certain Africanist discourse is preoccupied by the status of African thought, where Africa has been repeatedly construed as both unthinking and unthinkable. This highly original and groundbreaking book sets itself up against this tradition in readdressing questions of animism, hybridity and fetishism, in attending to a 'writing Africa': an Africa that reasserts and reinvents itself. The book marks in important contribution to colonial and postcolonial studies in its clarification of a particular Africanist discourse, and in its far-reaching analyses of the literature of animism. It will be of great critical interest to those working in philosophy, anthropology, literary and critical theory, politics and psychoanalysis."--BOOK JACKET.